(untitled) (Journal of Technical and Vocational Education and Training, 2021)
This paper analyses the challenges of the constitutional reform in Nepal and its impact on the governance of technical and vocational education and training (TVET). Thereby, the paper suggests five crucial recommendations. First, establish an Inter-Governmental TVET Council/Coordination committee, a high-level body with representatives of all three government levels. Second, describe the key TVET processes in a Master Plan that allocates tasks and processes to the appropriate level and supports a consistent federalisation process. Third, the high-level committee must address the remaining unclear normative issues in a TVET Policy for 2030 with goals and a vision for the sector. This should include allocating responsibilities to formal and non-formal education, defining what Nepal means by "good governance", defining the TVET programme approach, allocating detailed tasks to all three government levels and defining specific objectives for the TVET sector. Fourth, develop a TVET Act as quickly as possible. This is particularly important because the seven provinces depend on a national TVET legal framework to develop their own laws. Fifth, conduct a comprehensive TVET financial flows analysis to reconcile TVET funding sources and expenditures.